2022
DOI: 10.1111/cas.15250
|View full text |Cite
|
Sign up to set email alerts
|

Nanomedicine targets iron metabolism for cancer therapy

Abstract: Iron is an essential element for cell proliferation and homeostasis by engaging in cell metabolism including DNA synthesis, cell cycle, and redox cycling; however, iron overload could contribute to tumor initiation, proliferation, metastasis, and angiogenesis. Therefore, manipulating iron metabolisms, such as using iron chelators, transferrin receptor 1 (TFR1) Abs, and cytotoxic ligands conjugated to transferrin, has become a considerable strategy for cancer therapy. However, there remain major limitations for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 75 publications
(141 reference statements)
1
19
0
Order By: Relevance
“…With the rapid development of nanotechnology over the recent decades, engineered nanomaterials have been explored in biomedical and pharmaceutical applications, including drug delivery, molecular diagnosing, medical imaging, and disease therapy ( Zhao et al, 2020 ; Qin et al, 2021 ; Lin et al, 2022 ), which bring tremendous benefits to humans. The liver is the primary organ in metabolizing, biotransformation, and detoxifying drugs and exogenous substances, including nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of nanotechnology over the recent decades, engineered nanomaterials have been explored in biomedical and pharmaceutical applications, including drug delivery, molecular diagnosing, medical imaging, and disease therapy ( Zhao et al, 2020 ; Qin et al, 2021 ; Lin et al, 2022 ), which bring tremendous benefits to humans. The liver is the primary organ in metabolizing, biotransformation, and detoxifying drugs and exogenous substances, including nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of ferritin was weaker in the mice treated with 5-ALA than in those not treated with 5-ALA. Additionally, the expression of PCNA, which is specific to the S phase in cells, and not survivin, which is specific to the G2/M phase in cells, was higher in the mice treated with 5-ALA. Ferritin is a form of stored iron ( 1 , 6 ), and a decrease in ferritin results in a shortage of iron in bladder cancer cells. Therefore, the results of the in vivo study were consistent with those of the in vitro study.…”
Section: Discussionmentioning
confidence: 99%
“…Seligman et al ( 5 ) reported that bladder cancer cellular proliferation was dependent on iron. Therefore, chelating iron, such as desferrioxamine (DFO), has been evaluated for its antitumor effects ( 1 , 6 ), including in bladder cancer ( 5 ). Seligman et al ( 5 ) demonstrated that DFO inhibited proliferation of bladder cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The targeting lipid metabolism via nanotechnology provides a potential strategy to improve cancer therapy by regulating immune-metabolic signals. Although nanomedicines have been explored for tumor metabolism regulation (e.g., glycolysis and iron metabolism) ( Wang et al, 2019 ; Lin et al, 2021 ), it is still an infant field of applying nanotechnology for lipid metabolism regulation for immunotherapy.…”
Section: Perspectivesmentioning
confidence: 99%